Design and fabrication of a helmet washing machine - Mohd Fauzi, Muhammad Fuad Danish (2025)
Helmet is a protective headgear worn by individuals who ride motorcycles to protect the head from the impact or collisions. It is crucial to maintain a proper hygiene of a helmet to avoid any bacteria or unpleasant smell. However, the unique shape and attachment method of the interior of a helmet would make the cleaning process quite challenging. Therefore, this project is specifically designed to simplify and expedite the process of washing the helmet's inner part, ultimately saving time and effort from the user. The project adopts a methodical approach, involving concept generation by collecting all required information, followed by concept evaluation to add some improvements, product design using SolidWorks, meticulous material selection, prototyping, thorough testing, and adherence to safety standards. The significance of this project lies in its capacity to streamline the helmet cleaning process, eliminating the need for lengthy and burdensome procedures.